Do parallel pinning offer advantage over crossed pinning for displaced supracondylar humerus fractures in children: a randomized trial - Daral, Mayank; Vasu,; Agrawal, Himanshu; Bhargava, Rahul; Paridhi, (International Journal of Research in Orthopaedics, 2025)
Background: To compare outcomes between cross pinning with lateral pinning for fixation of displaced supracondylar fracture of humerus in children. Methods: Children (<12 years) with displaced supracondylar fractures of the humerus were randomized to receive either cross pinning (Group 1) or lateral pinning Group 2). Follow-ups were conducted at 3 weeks, 6 weeks, and 3 months. Clinic-radiological union, Baumann angle, loss of reduction, stability of fracture fixation, incidence of complications, and Flynn's score were compared. Results: The mean age of children in group 1 was 7.2±2.1 and in group 2 was 6.7±2.3, respectively (independent t-test, p=0.259). The mean follow up was 6.4±2.3 and 6.54±2.1 months, respectively (p=0.356). There were no significant differences observed in Baumann's angle, change in Baumann angle, loss of reduction, carrying angle, loss of carrying angle, range of motion in flexion and extension of the elbow, or total loss of range of motion between the two groups. One patient (2.4%) in group 1 had ulnar nerve injury. Based on Flynn's grading, 32 patients (85.7%) in group I and 27 patients (67.5%) in group II achieved excellent results (Figure 2b &c). In group I, 9 patients (31.4%) and in group II, 10 patients (25%) had good results. group I had 1 patient (2.4%) with fair results, while group II had 2 patients (5%) with fair results. One patient (2.5%) in group II had poor results. Conclusions: Both techniques ensure stable fixation, union, and good functional outcomes, except for iatrogenic ulnar nerve injury with cross pinning.